Transformational Leadership and Organizational Culture as Determinants of Sustainable Performance: A Strategic Management - Pamuji, Slamet; Deepak R Gupta (Forum Akademisi dan Dosen Peneliti (FAST), 2025)
This study investigates the role of transformational leadership and organizational culture as key determinants of sustainable performance within organizations from a strategic management perspective. By integrating transformational leadership practices such as inspirational motivation, intellectual stimulation, and individualized consideration with strong organizational culture, organizations can enhance operational efficiency, innovation, and long-term performance outcomes. The study highlights how the alignment of leadership style and cultural values fosters employee engagement, adaptive decision-making, and the effective implementation of strategic objectives. While these factors can drive sustainable performance, challenges may arise, including cultural resistance, misalignment between leadership and organizational values, and insufficient mechanisms to measure long-term outcomes. A strategic, phased approach emphasizing the development of leadership competencies, reinforcement of supportive cultural practices, and the use of integrated performance metrics can overcome these barriers and promote continuous improvement. Ultimately, transformational leadership combined with a robust organizational culture contributes not only to enhanced efficiency and performance but also to sustainable growth, competitive advantage, and a culture of excellence.